Experimental behaviour of RC beams shear strengthened with NSM CFRP laminates - Dias, Salvador J. E. (2012)
The near-surface mounted (NSM) is one of the most recent techniques applied for the increase of the shear resistance of reinforced concrete (RC) beams. This technique involves the installation of carbon fibre reinforcement polymers (CFRP) laminates into thin slits open on the concrete cover of the elements to strengthen. The effectiveness of this technique for the shear strengthening of T crosssection RC beams was assessed by experimental research. For this purpose, three inclinations of laminates were tested (45º, 60º and 90º) and, for each inclination, three percentages of CFRP were applied in RC beams with a percentage of steel stirrups of 0.10% (qsw). The highest percentage of laminates was designed to provide a maximum load similar to the reference RC beam, which was reinforced with a reinforcement ratio of steel stirrups of 0.28% (qsw = 0.28%). For each percentage of laminates, a homologous RC beam strengthened with unidirectional U-shaped CFRP wet lay-up sheets (discrete strips) applied according to the externally bonded reinforcement technique was also tested, with the purpose of comparing the effectiveness of these two CFRP-strengthening techniques. To evaluate the influence of the percentage of steel stirrups in the effectiveness of the NSM technique, some of the abovementioned CFRP configurations were also applied in beams with qsw = 0.17%